THE ANALYSIS OF SARCASM IN WEDNESDAY NETFLIX SERIES - Sakila Debora Saragih; Tiara K. Pasaribu; Donna Ria Pasaribu (Jurnal Widya, 2023)
This research is expected to improve people’s ability to use sarcasm in direct conversation or written, in addition to their ability to absorb new knowledge. The aims of this study are to find out the types of sarcasm used in Wednesday Netflix Series and to explain the function of sarcasm in Wednesday Netflix Series. this research is descriptive qualitative. Therefore, a research hypothesis is not used. This research examines the structure and significance of sarcastic language used by the characters of Wednesday in the Wednesday Netflix Series. In the research that the writer has done, of the four types in accordance with Camp’s theory, the types of sarcasm used by Wednesday are illocutionary, lexical, and propositional types. In the sarcasm function section, which amounted to 10 functions according to Keraf''s theory, the writer found the functions of affirmation, Affirmation, Prohibitions, Rejection, Submission of question, orders, opinions, comparison, information. it is possible to infer that the Wednesday Netflix series employs a significant degree of sarcasm in the conversation delivered by the Wednesday characters and as a sign to show who Wednesday is through her sarcastic way of speaking. The writer discovered various sarcastic phrases and context is a key tool for spotting sarcastic statements.